PENGARUH IMPLEMENTASI GAME INTERAKTIF TERHADAP PERILAKU KOMUNIKASI MASYARAKAT DI LINGKUNGAN KULINER LOKAL - Ramadan, Mohamad Faza Silmi; Zaliluddin, Dadan (Universitas Majalengka, 2025)
The rapid development of digital technology has influenced various aspects of life, including entertainment and social interaction. This practicum focuses on the development of an interactive game called Timbel Curhat at Warung Nasi Timbel Mista Cigasong as a medium for building positive communication between customers. The research method used is the Game Development Life Cycle (GDLC), which consists of the initiation, pre-production, production, testing, beta, and release stages. The testing method used is black-box testing to ensure functionality. The result of this practicum is an interactive game that encourages customers to communicate positively while waiting for or after enjoying their meal. The implementation of this game is expected to increase customer engagement, create a more enjoyable dining atmosphere, and strengthen social interaction among visitors.